Teenage mutant ninja turtles [videorecording (DVD)] : out of the shadows - Fox, Megan, 1986-; Arnett, Will; Perry, Tyler; Linney, Laura (Paramount, 2016)
After super villain Shredder escapes custody, he joins forces with mad scientist Baxter Stockman and two dimwitted henchmen, Bebop and Rocksteady, to unleash a diabolical plan to take over the world. As the Turtles prepare to take on Shredder and his new crew, they find themselves facing an even greater evil with similar intentions: the notorious Krang.